2019
DOI: 10.1002/anie.201905281
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the Space‐Charge Region of the FeNi‐LDH/CoP p‐n Junction to Promote Performance in Oxygen Evolution Electrocatalysis

Abstract: The modulation of electron density is an effective option for efficient alternative electrocatalysts. Here, p‐n junctions are constructed in 3D free‐standing FeNi‐LDH/CoP/carbon cloth (CC) electrode (LDH=layered double hydroxide). The positively charged FeNi‐LDH in the space‐charge region can significantly boost oxygen evolution reaction. Therefore, the j at 1.485 V (vs. RHE) of FeNi‐LDH/CoP/CC achieves ca. 10‐fold and ca. 100‐fold increases compared to those of FeNi‐LDH/CC and CoP/CC, respectively. Density fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
258
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 406 publications
(265 citation statements)
references
References 59 publications
6
258
0
1
Order By: Relevance
“…Besides, the C 1s peaks in HPCM‐5 exhibits a slight shift to lower one compared to MPCM (Figure 2e). These results further indicated that electrons transfer from Fe to N doped graphitic C at the heterojunction interfaces 6,9a,10,18. Overall, the charge regulation by Mott–Schottky effect in HPCM‐5 effectively causes electrons redistribution, forming a fast electron transfer path and enhancing ORR performance, which will be further discussed latter.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Besides, the C 1s peaks in HPCM‐5 exhibits a slight shift to lower one compared to MPCM (Figure 2e). These results further indicated that electrons transfer from Fe to N doped graphitic C at the heterojunction interfaces 6,9a,10,18. Overall, the charge regulation by Mott–Schottky effect in HPCM‐5 effectively causes electrons redistribution, forming a fast electron transfer path and enhancing ORR performance, which will be further discussed latter.…”
Section: Resultsmentioning
confidence: 68%
“…Mott–Schottky curve in Figure S12a, Supporting Information, indicated that the NG in HPCM‐5 is a p‐type semi‐conductor due to the negative slope and the flat band is 0.87 V versus Ag/AgCl 18. The flat band is similar to valence‐band maximum in p‐type semi‐conductor,28 so the top of valence‐band in NC in HPCM‐5 is calculate around 0.87 V versus Ag/AgCl (1.483 V vs RHE).…”
Section: Resultsmentioning
confidence: 99%
“…The calculated adsorption energies of CoMn/CoMn 2 O 4 for CO(NH 2 ) 2 and H 2 O are −2.2 and −3.57 eV, much lower than those of pristine CoMn 2 O 4 (Figure 5b), confirming the Schottky barrier region can enhance the adsorption probability and stability of urea and water molecules, namely, CO(NH 2 ) 2 and H 2 O have stronger trend to be adsorbed on the surface of the CoMn 2 O 4 side of CoMn/CoMn 2 O 4 Schottky heterostructure than the pure CoMn 2 O 4 , which is beneficial for the oxidation reaction. [ 45,47 ] Furthermore, the generated N 2 can be released more easily from the CoMn/CoMn 2 O 4 surface rather than the CoMn 2 O 4 surface due to the higher adsorption energy. Combining the catalytic mechanism analysis, these calculation results suggest that CoMn/CoMn 2 O 4 has an optimal electronic structure as a UOR catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the advantages of this 3D hierarchical binder-free structure, the abundant multimetallic catalytic sites of NiCoP and NiFe LDH promote the OER activity. Qian et al proposed a concept for promoting the catalytic activities for OER by constructing the FeNi-LDH/CoP/carbon cloth (CC) heterojunctions [125]. The self-supporting FeNi-LDH/CoP/CC electrode with an open and 3D hierarchical p-n junction structure is prepared through three steps including the electrodeposition of Co(OH) 2 nanosheets array on the CC, phosphatization of Co(OH) 2 , and electrodeposition of amorphous FeNi-LDH layers on the formed CoP array ( Fig.…”
Section: Construction Of 3d Freestanding Electrodes Based On Ldhsmentioning
confidence: 99%